2018
DOI: 10.14341/dm9583
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D deficiency in type 2 diabetes mellitus and diabetic neuropathy development

Abstract: Type 2 diabetes mellitus (DM) is a global epidemic associated with severe vascular complications development. Diabetic neuropathy is the most common chronic complication of DM that worsens patients life quality and prognosis. Therefore, studies dealing with DM and diabetic neuropathy underlying mechanisms are extremely relevant. The review discusses current views on vitamin D role in glucose metabolism and inflammatory processes. It is reported that vitamin D deficiency can contribute to insulin resistance dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Vitamin D deficiency has been shown to affect diabetic complications by influencing glucose metabolism and inflammatory process [3,33]. Pleiotropic effect of vitamin D on inflammation has been found to play an important role in DPN development, and it is of great scientific and practical interest [34]. Some studies have shown higher TNFα and lower IL-10 levels associated with increased HbA1c in patients with T2DM and DPN than in patients with impaired glucose tolerance and healthy controls [35].…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin D deficiency has been shown to affect diabetic complications by influencing glucose metabolism and inflammatory process [3,33]. Pleiotropic effect of vitamin D on inflammation has been found to play an important role in DPN development, and it is of great scientific and practical interest [34]. Some studies have shown higher TNFα and lower IL-10 levels associated with increased HbA1c in patients with T2DM and DPN than in patients with impaired glucose tolerance and healthy controls [35].…”
Section: Discussionmentioning
confidence: 99%